A framework to review performance measurement systems. - Najmi, Manoochehr; Rigas, John; Fan, Ip-Shing (Emerald Group Publishing Limited, 2005)
This paper describes a structured review framework for managing business performance. The framework entails the review of both business performance, including thestrategic relevance of the measures, as well as the efficiency and effectiveness of the performance measurement system itself. A range of approaches and tools are employed in the framework which features a review card providing a high level view of the review process, showing the different types of review perspectives and their interactions.